The advancement of nanosystems for drug delivery in the prevention and treatment of dental caries - Han Du; Zheng Wang; Shenglan Long; Yiding Li; Deqin Yang; Deqin Yang; Deqin Yang (Frontiers in Cellular and Infection Microbiology)
The dental caries remains a globally prevalent disease. Although its incidence has decrease due to enhancements in sanitation policies and public health measures, the treatment and prevention of dental caries still pose significant challenges. Within the oral cavity, traditional drug delivery systems suffer from limitation such as inadequate tissue penetration, short duration of action at target site, and low specificity, which minimally affect the prevention and treatment of dental caries. Consequently, nanosystem for drug delivery, offering enhanced drug stability, solubility, and bio-availability while reducing side effects, garnering attention increasing attention in the fight against dental caries. Therefore, this review examines the role of nanosystems for drug delivery in combating dental caries by inhibiting bacteria survival, biofilm formation, demineralization, and promoting remineralization, and exploring their potential to become the mainstream means of prevention and treatment of dental caries in future.